Responses of clover and desmodium to Egyptian rockphosphate in Ethiopia - Haque, I.; Lupwayi, N.Z. (1999)
Although the majority of soils in Africa are P deficient, the high cost of conventional water-soluble P fertilizers limits their use by resource-poor farmers. Rockphosphates are a low-cost alternative. The effect of Egyptian rockphosphate (ERP) from two sources, applied at 50 kg P ha-1, on annual Trifolium tembense (clover) grown on a Vertisol was evaluated. The fertilizers were applied once and their effects were followed on five consecutive annual clover crops. Clover responded to P from either source of ERP, with no significant difference between the two sources. Significant (P<0.05) P effects on clover P uptake and dry matter yields were observed up to the third croThe effect of mixing TSP with ERP on yields of Desmodium sanduicause was also evaluated on an Alfisol. Mixtures containing 1:1 and 1:3 ratios of TSP:ERP on the basis of P content, gave the highest yields, but these were not significantly higher than those from ERP applied alone. Therefore, mixing ERP with the more expensive TSP is not justified. Use of rockphosphates alone could elevate the P status of the P-deficient soils and increase forage and livestock productivity in the Ethiopian highlands.